Oleanane-type triterpenoid saponins from Silene armeria - Takahashi, Nobuyuki; Li, Wei; Koike, Kazuo (Phytochemistry (Oxford), 2016)
Twelve triterpenoid saponins, including seven compounds (i.e., armerosides A–G) hitherto unknown, were isolated from whole plants of Silene armeria. Their structures were established based on extensive spectroscopic analyses and chemical methods. From a biosynthetic perspective, C-23 oxidation of the sapogenin appears to be a key factor in the glycosylation pathway. [Display omitted] •Twelve triterpenoid saponins, five previously known, were isolated from Silene armeria.•Two possess a unique 3,4-seco-oleanane sapogenin structure.•Oxidation of C-23 of the sapogenin is a key factor in Silene saponin biosynthesis.